Temperature‐driven changes in the diet preference of omnivorous copepods: no more meat when it's hot? A response to Winder et al. (9th September 2016) - Boersma, Maarten; Mathew, K. Avarachen; Niehoff, Barbara; Schoo, Katherina L.; Franco‐Santos, Rita M.; Meunier, Cédric L.
Abstract: The study of environmental impact on feeding preferences of omnivores is a rapidly growing field. Here, we show that the criticism put forward in a comment on our original study is largely unfounded.